Investigations of the sciences of the Qur'an in the interpretation of Al-Maraghi and its impact on explaining the meaning of the verse: Analytical study - Maher Bin Ghazali (Rabbanica: Journal of Revealed Knowledge)
This study attempts to explore the sciences of the Qur'an by evaluating Ahmed Al-Maraghi's interpretation and assessing how it affects the verse's meaning. Given the significance of this interpretation and the range of scientific topics it covered, Ahmed Al-Maraghi is one of the modern interpreters and a member of the reformist school of interpretation. To achieve this, the researcher employed the inductive approach to extrapolate and systematically analyze books and literature on the sciences of the Qur'an, and the interpretation of Ahmed Al-Maraghi. The research has discovered the sciences of the Qur'an detectives that are directly related to the meaning of the verse is also related to the revelation of the verse, the reason for its descent, and the meaning of the verse. Ahmed Al-Maraghi is considered one of the contemporary interpreters who was interested in the investigations of the sciences of the Qur'an in his interpretation, although he did not refer to this in the introduction to his interpretation. It also appeared to us that one of the investigations of the sciences of the Qur'an in the interpretation of Al-Maraghi, which affects the meaning of the Makki and Madani verse, and the reasons for the descent, the number of verses, the strange Qur'an, and the ambiguities of the Qur'an, while those that do not affect the meaning of the verse, they are the names of the surahs, the virtues of the surahs, and the occasions between the surahs.